Pembangunan Tempat Sampah Sementara Di Desa Bolihutuo Kecamatan Botumioto Kabupaten Boalemo - Safrudin Tolinggi; Moh. Rivandi Dengo; Franning Deisi Badu; Marselia Sandalayuk; Aulia Anisa (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
Disposing of household waste carelessly around the house or into the river has become a habit for some people in Bolihutuo Village, causing several environmental-based diseases and polluting the river. Therefore, it is necessary to conduct a study on household waste management based on operational technical aspects, institutions, financing, laws and regulations and community participation. This observational analytic study aims to examine household waste management and the factors related to it, as well as to plan community-based household waste management. The result is that the average household waste generated is 1.46 litters/person/day or 0.38 kg/person/day, which consists of 47% organic waste, 15% paper, 22% plastic, and 16% metal and others. In Bolihutuo Village has not been implemented optimally. Education level, income level, behaviour towards environmental hygiene, knowledge of regional regulations on solid waste, and willingness to pay waste fees are positively correlated with household waste management. Suggestions given include improving waste services, forming village waste management groups, involving the community and the private sector in financing, increasing cross-sectoral coordination and involving community leaders and religious leaders, and implementing strict solid waste regulations.